Facts about Potassium - R. Elaine Turner; Linda B. Bobroff (EDIS)
Revised! FCS8805, a 2-page handout by R. Elaine Turner and Linda B. Bobroff, provides basic facts about the electrolyte potassium in an easy-to-read format. Published by the UF Department of Family Youth and Community Sciences, March 2010.